IMPACT OF MACROECONOMIC VARIABLES ON STOCK RETURN VOLATILITY: EVIDENCE FROM SUB-SAHARA AFRICA - Peter, Ali Ifeanyichuwkwu; Nzotta, Samuel M.; Akujuobi, A. B. C.; Nwaimo, Chilaka E. (Journal Economics & Business Atmajaya Indonesia, 2020)
The main purpose of this paper was to investigate the impact of macroeconomic variables on stock market return volatility in Sub-Sahara markets. The study concentrated on three stock markets including Ghana, Nigeria and South Africa using GARCH-X (1,1) model on monthly data from January 2000 to December 2017. Preliminary analyses from descriptive statistics show that mean monthly returns are positive for all the stock markets. Skewness coefficients show that the stock returns and interest rates distribution of all Sub-Sahara Africa stock markets are negatively skewed but inflation rate is positively skewed for Nigeria and South Africa, and flat for Ghana. Excess kurtoses are positive for all the stock markets and macroeconomic indicators, and Jarque-Bera statistics indicate the stock markets’ series and macroeconomic indicators are not normally distributed. The Unit roots tests results indicate that all the stock markets and macroeconomic indicators are first difference stationary. The results of the GARCH-X (1,1) model show that macroeconomic variables do not significantly impact stock market returns volatility in Nigeria, Ghana and South Africa at the 5% significance Level. We therefore recommend that stock market regulators, market participants and investors should concentrate more efforts on other macroeconomic variables aside interest rate and inflation rate, in estimating stock market return volatility in Sub-Sahara Africa.